Answer:
[tex] P(E) =0.25, P(F) = 0.40, P(E \cap F) =0.05[/tex]
[tex] P(E \cup F)= P(E) +P(F) -P(E \cap F)[/tex]
And replacing we got:
[tex] P(E \cup F)=0.25 +0.40 -0.05 = 0.6[/tex]
Step-by-step explanation:
For this case we have the following probabilities given:
[tex] P(E) =0.25, P(F) = 0.40, P(E \cap F) =0.05[/tex]
And we want to find this probability:
[tex] P(E \cup F)[/tex]
And we can use the total probability rule given by:
[tex] P(E \cup F)= P(E) +P(F) -P(E \cap F)[/tex]
And replacing we got:
[tex] P(E \cup F)=0.25 +0.40 -0.05 = 0.6[/tex]